Diagnosing the potential of hydro-climatic information services to support rice farming in northern Ghana. (1st November 2018) - Nyadzi, Emmanuel; Nyamekye, Andy B.; Werners, Saskia E.; Biesbroek, Robbert G.; Dewulf, Art; Slobbe, Erik Van; Long, Hoang P.; Termeer, Catrien J.A.M.; Ludwig, Fulco
Abstract: Hydro-climatic information has a potential to improve agricultural productivity under climate variability. Recent developments in information sharing platforms (Environmental Virtual Observatories, EVOs) could make information provisioning more actionable. Here we present the results of a diagnostic study for the development of a hydro-climatic EVO that enables rice farmers in Northern Ghana to deal with climate variability and water shortage. The hydro-climatic EVO aims to combine data from scientific and indigenous forecast systems, facilitating information exchange using two-way interaction with stakeholders to co-produce knowledge. Data was collected through informal interviews with field practitioners, through focus group discussions with farmers and content analysis of documents. Results show that both the biophysical and socio-institutional circumstances need be taken into account for the development of the EVO. Existing governance and information exchange arrangements and lack of collaboration between actors were found to limit current hydro-climatic information flow, interpretation, and use. Our study reveals existing models of information exchange and their limitations in the study area. We discuss the proposed design of a hydro-climatic EVO from a responsible innovation perspective, considering possible future eventualities in a process that aims to be anticipatory, inclusive, reflexive and responsive. We conclude that such a hydro-climatic EVO has a potential to contribute to rice farmers' adaptive decision-making in Northern Ghana, but there are challenges that need to be considered. The diagnostic study has helped to refine these challenges and offers concrete suggestions to improve both the design and implementation of the proposed platform in a responsible way.